The degree of inclusion of higher-order thinking skills in the mathematics textbook for the first year of secondary school in Kingdom of Saudi Arabia - Al-Shehri, Amal Ali Muhammad (Journal of Curriculum and Teaching Methodology, 2024)
The study aimed to identify the extent to which higher-order thinking skills are included in the mathematics textbook for first-year high school students in Saudi Arabia. Using the descriptive-analytical methodology, the research tool was a content analysis form prepared by the researcher. The analysis covered all 13 chapters of the book. The study revealed that the inclusion of higher-order thinking skills in the mathematics textbook was at a moderate level (40%). Among the skills, creative thinking was most prevalent, followed by critical thinking, problem-solving, and decision-making, which was included at a very low level. The results showed that most sub-skills of critical thinking (interpretation, inference, analysis, evaluation) ranged from low to very low across all chapters, except for classification and comparison skills, which were moderately included. As for the sub-skills of creative thinking, fluency ranked first, followed by flexibility, and lastly originality, all at very low levels. Based on these results, the researcher recommended increased efforts to incorporate higher-order thinking skills in the first-year high school mathematics textbook, especially decision-making, evaluation within critical thinking, and originality within creative thinking.